2019
DOI: 10.1016/j.semcancer.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Ras and Rap1: A tale of two GTPases

Abstract: Ras oncoproteins play pivotal roles in both the development and maintenance of many tumor types. Unfortunately, these proteins are difficult to directly target using traditional pharmacological strategies, in part due to their lack of obvious binding pockets or allosteric sites. This obstacle has driven a considerable amount of research into pursuing alternative ways to effectively inhibit Ras, examples of which include inducing mislocalization to prevent Ras maturation and inactivating downstream proteins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 223 publications
(261 reference statements)
2
116
0
Order By: Relevance
“…RAP1 (Ras-related protein 1) signalling pathway was identified as enriched in deiminated proteins in whole bovine serum. It belongs to a superfamily of small GTPases, with pleiotrophic regulatory functions in cellular processes, such as nuclear transport, cell cycle progression, vesicle trafficking, cell adhesion and cytoskeletal rearrangement [217]. Rap1 is an inflammatory regulator, is highly expressed in platelets and is a key molecule for platelet activation and adhesion in injury [218,219].…”
Section: Discussionmentioning
confidence: 99%
“…RAP1 (Ras-related protein 1) signalling pathway was identified as enriched in deiminated proteins in whole bovine serum. It belongs to a superfamily of small GTPases, with pleiotrophic regulatory functions in cellular processes, such as nuclear transport, cell cycle progression, vesicle trafficking, cell adhesion and cytoskeletal rearrangement [217]. Rap1 is an inflammatory regulator, is highly expressed in platelets and is a key molecule for platelet activation and adhesion in injury [218,219].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, IKZF1 deficiency in BPDCN might underlie or contribute to the observed overactivation of the PI‐3‐K/Akt pathway. In contrast, the Rap1 pathway regulates cell motility and integrin‐mediated adhesion in leukocytes, lymphocytes and dendritic cells, both of which are processes hijacked by neoplastic cells to disseminate to other body sites . In fact, activation of Rap1 signaling has been shown to trigger migration of T‐acute lymphoblastic leukemia and B‐cell lymphoma cells, in vitro and in vivo, respectively …”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of CNAs involving IKZF1 was lower in the extension cohort compared to the sequenced cohort (difference not statistically significant, P > .05, Fisher's exact test), patients with normal IKZF1 copy number might still carry inactivating balanced to disseminate to other body sites. 51 In fact, activation of Rap1 signaling has been shown to trigger migration of T-acute lymphoblastic leukemia and B-cell lymphoma cells, in vitro and in vivo, respectively. 52,53 We found that genes silenced by PRC2 (EZH2) were the most over- Table S16 for a complete list of enriched terms/ processes).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, here we showed that altered levels of human Rap1a impacted the migration speed of GBM CSCs. Accumulating evidence indicates a general role for Rap1a in the cell migration and invasion of a variety of tumors 64,66 . Depending on the cancer, either elevated or decreased Rap1a activity enhances or suppresses tumor invasion, typically through regulation of either cadherinor integrin-based adhesions 66 .…”
Section: Interestingly Rap1 In Border Cells Also Keeps the Cells In mentioning
confidence: 99%
“…Accumulating evidence indicates a general role for Rap1a in the cell migration and invasion of a variety of tumors 64,66 . Depending on the cancer, either elevated or decreased Rap1a activity enhances or suppresses tumor invasion, typically through regulation of either cadherinor integrin-based adhesions 66 . This suggests complex roles for Rap1a and the downstream molecular pathways and effectors, which likely depend on the tumor type and cellular context 64 .…”
Section: Interestingly Rap1 In Border Cells Also Keeps the Cells In mentioning
confidence: 99%